ECTOPIC PREGNANCY: RISK FACTORS, A PROBLEMS OF DIAGNOSIS, TREATMENT, THE RESTORATION OF FERTILITY - Лариса Егоровна Фетищева; Галина Александровна Ушакова; Любовь Никитична Петрич (The Publishing House Medicine and Enlightenment, 2017)
Despite major advances in the diagnosis and treatment of gynecological diseases, the problem is ectopic pregnancy remains relevant. An ectopic pregnancy is one of the leading places in the structure of maternal mortality is in the first place as a cause of intra-abdominal bleeding and second place in the structure of gynecological diseases. At least half of the emergency surgical interventions in gynecological practice is the operation associated with interrupted ectopic pregnancy. Despite progress in diagnosis and methods of surgical treatment of ectopic pregnancy fails to reduce the frequency of this pathology and complications associated with it. This review considers current approaches to the diagnosis, treatment and recovery of fertility of ectopic pregnancy.